Reconceptualization of Land Acquisition Regulations for Tourism Village Development Based on the Principle of Public Interest - Wardana, Azna Abrory; Koeswahyono, Imam; Permadi, Iwan; Prasetyo, Ngesti Dwi (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
Villages hold a strategic position in harnessing tourism potential as part of regional autonomy at the regency and city levels. Such development efforts can yield substantial economic gains and enhance the welfare of local communities. Despite this, the existing legal framework confines the authority to carry out land acquisition for tourism area development solely to four entities: the central government, regional administrations, state-owned enterprises (“BUMN”), and regionally owned enterprises (“BUMD”). As a result, village governments and village-owned enterprises face limitations in developing village tourism areas. This study employs a normative juridical approach, integrating conceptual and statutory methods. The findings indicate that strengthening decentralization and focusing on rural development present opportunities to empower village governments and village-owned enterprises with the authority to acquire land. The restriction of land acquisition for tourism areas to the central government, regional governments, SOEs, and ROEs is becoming increasingly irrelevant. Village tourism areas possess more significant economic potential when managed directly by village governments and village-owned enterprises, with active involvement from local communities. Therefore, a legal reconstruction is necessary to expand the entities authorized to acquire land for village tourism development. This can be achieved by harmonizing relevant legislation, particularly Law No. 2 of 2012, in conjunction with Law No. 6 of 2023 and Government Regulation No. 11 of 2021. Such harmonization will support village governments and village-owned enterprises in realizing effective, sustainable, and inclusive village tourism development.